(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Extracts of herbal plant samples which include leaves and seeds of Calotropis procera and Garcinia kola respectively were investigated for phytochemical content and tested against clinical isolates of Mycobacterium tuberculosis (in-vitro). 95% methanolic extract of the plant samples were obtained by percolation. The anti-mycobacterial activity was determined using disc diffusion method; Anova single factor was statistically used for the analysis. The crude methanol extract of Calotropis procera leaf and Garcinia kola seed reveal a final weight of 8.1g and 19.1g, tannins and flavonoids were the phytochemical compounds found to be present in all the plant samples. Rifampicin antibiotic was used as control and the antimycobacterial activity for the plant sample shows that C. procera has the highest zone of inhibition followed by G. kola, the minimum inhibitory concentration ranging from 500-2000ug/ml. The M.I.C of 95% methanol extract in the order mention above are 500-2000ug/ml and 1000-2000ug/ml. The result support the local use of these plants in the treatment of tuberculosis and it is suggested that these plants may have therapeutic value in the treatment of Tuberculosis. However, further investigations should be focused toward isolating chemical constituent that are responsible for pharmacological activities and identifying the compound eliciting the activities observed in the plant samples